2022
DOI: 10.3389/fonc.2022.763341
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 Inhibits the Migration and Invasion of Lung Adenocarcinoma by Negatively Regulating the FAM83D-TGFβ1-SMAD2/3 Pathway

Abstract: ObjectiveYTH domain family 2 (YTHDF2) is an important N6-methyladenosine (m6A) reader, but its role in lung adenocarcinoma remains elusive. This study assessed its function in lung adenocarcinoma.MethodsYTHDF2 expression in lung adenocarcinoma was explored using public databases, such as The Cancer Genome Atlas (TCGA) and the Clinical Proteomic Tumour Analysis Consortium (CPTAC). The effect of YTHDF2 on a lung adenocarcinoma cell line was explored by performing cytological and molecular experiments. Molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…EGFR is the target of YTHDF2 and inhibits the proliferation and growth of HCC cells by mediating the MEK/ERK pathway 13 . In addition, YTHDF2 is also engaged in the TGFB1-PSMad 2/3 pathway and the AKT pathway, these pathways can induce the proliferation and migration of pterygium broblast 23,24 . Whether these pathways are involved in the proliferation and migration of pterygium deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is the target of YTHDF2 and inhibits the proliferation and growth of HCC cells by mediating the MEK/ERK pathway 13 . In addition, YTHDF2 is also engaged in the TGFB1-PSMad 2/3 pathway and the AKT pathway, these pathways can induce the proliferation and migration of pterygium broblast 23,24 . Whether these pathways are involved in the proliferation and migration of pterygium deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…WTAP is expressed at low levels in LUAD tissues, and it was shown that PCGEM1 can accelerate the progression of NSCLC by inducing miR-433-3p to upregulate WTAP, [ 26 ] This demonstrates that WTAP is a risk factor for lung cancer YTHDF2 inhibits LUAD cell migration and invasion through regulation of the FAM83D-TGFβ1-pSMAD2/3 pathway, suggesting that YTHDF2 is a lung cancer suppressor [ 27 ] Although WTAP and YTHDF2 have been shown to correlate with response to anti-PD1 therapy in hepatocellular carcinoma. [ 28 ] However, the relationship between WTAP and YTHDF2 expression and immunotherapy response in LUAD patients remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chang et al, YTHDF3 promotes breast cancer brain metastasis by inducing the upregulation of ST6 N-acetylgalactosaminide alpha-2,6-sialyltransferase 5 (ST6GALNAC5), gap junction protein (GJA1), and EGFR, whose transcripts are enriched in m 6 A modifications [96]. The inhibitory effect of YTHDF2 on the metastasis of lung adenocarcinoma was also investigated [97].…”
Section: Methyladenosine Modifications In Metastasismentioning
confidence: 99%